2014
DOI: 10.1111/jbi.12296
|View full text |Cite
|
Sign up to set email alerts
|

Hopping out of Mindanao: Miocene‐Pliocene geological processes and cross‐island dispersal as major drivers of diversity for Philippine treehoppers

Abstract: Aim We investigated the biogeographical history of an endemic Philippine treehopper, Pyrgonota bifoliata (Membracidae), to test the effect of Neogene geological events and Pleistocene climate change in generating speciation within the Philippines.Location The Philippine archipelago.Methods Phylogenies were reconstructed based on the mitochondrial cytochrome c oxidase I subunit (cox1) and nuclear wingless (wg) genes using maximum parsimony, maximum likelihood and Bayesian criteria. Divergence times were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…These changes could provide many chances to make the ancestors of Philippine Centromeria disperse to the Philippine Islands, although the dictyopharid species are not supposed to possess the ability of long‐distance dispersal. In addition, the historical dispersal of Centromeria species to adjacent islands might also have been promoted by drifting floating vegetation of host plants along oceanic currents, resulting in the passive transport of adults, nymphs, and/or eggs inserted in the tissues of host plants, like the Philippine treehoppers (Su et al ., ), or by wind‐assisted migration, as has been observed in the migratory planthoppers (Anderson et al ., ).…”
Section: Discussionmentioning
confidence: 84%
“…These changes could provide many chances to make the ancestors of Philippine Centromeria disperse to the Philippine Islands, although the dictyopharid species are not supposed to possess the ability of long‐distance dispersal. In addition, the historical dispersal of Centromeria species to adjacent islands might also have been promoted by drifting floating vegetation of host plants along oceanic currents, resulting in the passive transport of adults, nymphs, and/or eggs inserted in the tissues of host plants, like the Philippine treehoppers (Su et al ., ), or by wind‐assisted migration, as has been observed in the migratory planthoppers (Anderson et al ., ).…”
Section: Discussionmentioning
confidence: 84%
“…The identification of factors leading to speciation and elucidation of the associated mechanisms generating biodiversity are considered to be important tasks by evolutionary biologists (Schluter & Pennell, ). Previous studies targeting various taxa demonstrated that the origins of genetic diversity, evolution and speciation are the results of complex interactions among geographical history, random genetic drift, the environment, biological factors, and stochastic processes (Hoskin, Higgie, Mcdonald, & Moritz, ; Kano, Nishida, & Nakajima, ; Komaki et al, ; Saito & Tojo, ; Schoville, Uchifune, & Machida, ; Su, Wang, & Villanueva, ; Suzuki, Kitano, & Tojo, ). In particular, the fragmentation of populations is one of the major factors driving diversification and speciation often as the result of (a) climate changes within habitats and (b) changes in the environmental conditions between habitats thereby promoting divergent adaptation (Cole et al, ; Jensen et al, ; Schoville & Roderick, ; Shi, Ji, Liu, Wang, & Zhang, ; Stewart, Lister, Barnes, & Dalén, ; Tojo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The complex and dynamic geological history of the Philippines, characterized by extensive tectonic movement and volcanic activity gradually shaping the archipelago over the last c . 30 Myr (Hall, ; Yumul, Dimalanta, Maglambayan, & Marquez, ), has been cited as an important driver of diversification in the archipelago (Brown et al., ; Esselstyn, Timm, & Brown, ; Heaney, ; Heaney, Balete, & Rickart, ; Jansa, Barker, & Heaney, ; Su, Wang, Villanueva, Nuñeza, & Lin, ). More recently, Pleistocene climate cycles may have played a prominent role in promoting speciation in the Philippines, with numerous studies citing the effects of sea level fluctuations in fostering the dispersal and diversification of terrestrial organisms across the archipelago (Brown et al., ; Esselstyn & Brown, ; Heaney, , ; Roberts, ).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, fewer studies have examined the importance of intra‐island diversification, which could have played a significant role in generating diversity on the larger and more topographically complex islands in the Philippines (Heaney, ; Kisel & Barraclough, ; Whittaker et al., ). Evidence indicating the potential importance of intra‐island speciation in the Philippines has emerged from research on birds (Hosner, Nyari, & Moyle, ; Hosner, Boggess, et al., ), skinks (Linkem, Diesmos, & Brown, ), treehoppers (Su et al., ), shrews (Esselstyn et al., ), and murid rodents (Balete, Rickart, Heaney, & Jansa, ; Balete et al., ; Heaney, Balete, Rickart, & Jansa, ; Heaney et al., ; Justiniano et al., ; Steppan, Zawadski, & Heaney, ), with many of these studies implicating the numerous ‘sky islands’ on Luzon and Mindanao as important drivers of diversification. The extent to which such intra‐island processes represent the rule or exceptions in the Philippines, however, remains inadequately assessed.…”
Section: Introductionmentioning
confidence: 99%